Person - Centred Counselling in Action - Mearns Dave; Thorne Brian (Sage, 2013)
This book is an invaluable resource for those embarking on their first stages of training. Well - established practitioners and even seasoned scholars will continue to find much to interest and stimulate them. Acknowledgements, Introduction, Basic Theory of the Person - Centred Approach, Recent Developments in Person - Centred Theory, The Counsellor's Use of the Self, Empathy, Unconditional Positive Regard, Congruence, Beginnings, Middles, Endings, Research on Person - Centred Counselling, Appendix: Questions and Responses, References, Index of Names and Subject.